Analisis Kinerja Protokol Ad Hoc On-Demand Distance Vector (AODV) dan Fisheye State Routing (FSR) pada Mobile Ad Hoc Network - Desy Ulina Purba; Rakhmadhany Primananda; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The development of ad-hoc network technology is Mobile Ad-Hoc Network (MANET). MANET is formed from a collection of nodes that use wireless interfaces to be able to communicate between nodes with other nodes. Each node has the same position, so it takes a routing protocol that able to cover the exchange of data to be able to provide an optimal routing path. In this research, routing protocols used are AODV and FSR. AODV routing protocol establishes a route from one source node to the destination node based on the request of the source node. FSR routing protocol, each node stores a table containing route information on each node that it knows, route information will be updated regularly in case of link changes. Parameters of routing protocol performance measured in the form of packet delivery ratio, end to end delay, throughput and packet loss using Network Simulator 2.35. The results obtained in this research are FSR protocols best at the value of throughput parameters with an average value of 108,435 kbps and end to end delay with an average value of 16.06575 m/s. AODV protocol, best at the value of packet delivery ratio with an average value of 98.95 % and packet loss with an average value of 1.05 %. AODV protocol routing and FSR protocols have their respective advantages over each protocol based on Quality of Service (QoS) performance values ​​on the addition of nodes and packet size variations.